(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Fabric thickness and texture directly affect heat and moisture transfer characteristics in the human body-fabric-environment system, which determine the heat-moisture comfort level of the human body. Based on the model of steady-state heat and moisture transfer from skin to environment, we put forward an Inverse Problem of Thickness-texture Determination (IPTTD). Adopting the idea of the least-squares method, we formulate IPTTD into a function minimization problem. We employ Particle Swarm Optimization (PSO) method to directly search optimal solution of the objective function. The results of numerical simulation show the effectiveness of the presented algorithms and validity of the proposed IPTTD.